Prognostic significance of elevated pre-treatment serum CA-125 levels in patients with stage I ovarian sex cord-stromal tumors. (July 2019) - Nasioudis, Dimitrios; Wilson, Elise; Mastroyannis, Spyridon A.; Latif, Nawar A.
Abstract: Objective: To investigate the prognostic significance of elevated pre-operative serum CA-125 values for patients with early stage ovarian sex cord – stromal tumors (SCSTs). Methods: Patients diagnosed between 2004 and 2015 with a SCST were drawn from the U.S National Cancer Database. Those with stage I disease, and normal or elevated CA-125 values were selected for further analysis. Overall survival (OS) was evaluated for patients diagnosed between 2004 and 2014 with Kaplan-Meier curves, and compared with the log-rank test. A multivariate Cox analysis was performed to control for known confounders. Results: A total of 1156 patients met the inclusion criteria; 486 (42%) had elevated pre-treatment CA-125 values. Patients with elevated pre-treatment CA-125 (n = 417) had worse OS compared to those with normal values (n = 588), p < 0.001 from log-rank test; 5-yr OS rates were 86.8% and 94.8% respectively. After controlling for patient age (<50 vs > = 50 yrs), the presence of medical co-morbidities, tumor histology (granulosa vs non-granulosa), size (<10 vs > = 10 cm vs unknown) and the performance of lymphadenectomy, elevated pre-treatment CA-125 levels were associated with a worse survival (HR: 1.80, 95% CI: 1.15, 2.82, p = 0.01). Conclusions: In a large cohort of patients with early stage SCSTs elevated preoperative CA-125 levels were associated with worse survival.